PENGARUH KONTROLER MAXIMUM POWER POINT TRACKING (MPPT) TERHADAP EFISIENSI DAYA VERTICAL AXIS WIND TURBINE (VAWT) TIPE SAVONIUS DUA SUDU - Wardana, Catur; Siswantoro, MT., Ir. Soeadgihardo; ., Dr. Sugiyanto, S.T., M.Eng (Program Studi Magister Energi, Sekolah Pascasarjana, Universitas Diponegoro, Indonesia, 2023)
The purpose of this research is to determine the effect of Maximum Power Point Tracking (MPPT) controller on the power efficiency of a two-bladed Savonius vertical axis wind turbine (VAWT) with a dimensional diameter of 0.9 m and a height of 1 meter, using 1 mm thick stainless steel plate blades. The MPPT controller is applied to the two-bladed Savonius wind turbine to maintain its operation at the maximum power point. The Perturb & Observe type MPPT controller is used in the study to compare the power output of the Savonius wind turbine when the MPPT system is inactive and when it is active, with three variations of load using resistors of 470 ohm, 560 ohm, and 1000 ohm. The research is conducted by subjecting the turbine blades to three variations of wind thrust at speeds of 4.9 m/s, 5.8 m/s, and 6.4 m/s. The testing without using MPPT resulted in an average power of 0.199 Watt, while using MPPT resulted in an average power of 0.620 Watt. The research findings indicate an average power difference of 0.421 Watt, representing an increase of 317.713%. The average power efficiency of the turbine increased by 2.331% compared to the calculated maximum power of the two-bladed Savonius wind turbine. The average power coefficient (Cp) of the two-bladed Savonius wind turbine without MPPT and with MPPT is 0.159% and 0.509%, respectively, indicating a positive effect of MPPT as it led to an average increase in power coefficient of 0.350%.